Examining teachers’ perceptions and attitudes of Japanese use in the English classroom - Aiken, K (2022)
In Japan, English has been a compulsory school subject from Year 5 of elementary school since 2011 (Japanese Ministry of Education, Science and Culture, 2008). English conversation schools and after school programs have also become increasingly popular. To help bolster Japan’s English education, many public and private schools alike have marketed English-only instruction or “No Japanese” environments as the best way to facilitate learning to children. However, in Japan and across the world, teachers may not always be willing or able to carry out such curricula or policies. Using a mixed methods approach, this paper aimed to uncover how teachers at various teaching establishments in Japan feel about banning the use of Japanese in the English classroom. Through an online questionnaire, in-class observations, and teacher interviews, participants were asked if and when they use their students’ first language (Japanese) and how they view their current teaching situation as well as their ideal situation. Correlation analysis of the questionnaires showed that the age of students taught was related to how much teachers use Japanese in the classroom. It also uncovered that the teachers’ school’s policy showed some relationship to how the teacher viewed using Japanese. In other words, teachers with more liberal views of first language use in the classroom tended to work for schools that shared those views or supported first language use in the curriculum. Qualitative analysis of the observations and interviews showed that a teacher’s education and experience may influence their opinions as well. Although the data collected was limited due to the restraints of the COVID-19 pandemic, this paper highlights the trend that English-only may not be favored by all teachers and may not be entirely realistic within the contexts of English education in Japan.